Evaluating kansei emotion responses in human-robot interaction with low-cost robots in educational setting - Syamimi, Shamsuddin; Azmin, Ahmad Faris; Mat Ali, Mahasan; Kamat, Seri Rahayu; Maharof, Madihah; Yussof, Hanafiah (Penerbit UTeM, 2023)
Recent studies on human-robot interaction (HRI) is rapidly revolving. In a kindergarten setting, robots can become an important social interface for children, but the cost involved in implementing such robots can be high. This study aims to explore children’s emotional responses when interacting with RoboBuilder (a humanoid) and My Keepon (a toy-like robot) in a kindergarten setting. Both are inexpensive robots. Four children aged four and five years old took part in the HRI observation. Firstly, the children were exposed to a RoboBuilder dancing to a musical tune. The children then interacted with My Keepon by touching it and responding to its sounds. Videos of interactions were analyzed and scores were assigned based on eight Kansei emotion parameters. Results revealed that the children’s responses were favorable and they felt comfortable interacting with both robots. However, the children were more drawn to interact with My Keepon due to its toy-like design and cute appearance compared to RoboBuilder. Outcome through Kansei engineering approach shows that HRI involving a robot with adorable features is more appealing to children in the kindergarten setting.